2021
DOI: 10.3390/app11178268
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Umami Dry-Cured Ham-Derived Dipeptide Interaction with Metabotropic Glutamate Receptor (mGluR) by Molecular Docking Simulation

Abstract: Dry-cured ham-derived dipeptides, generated along a dry-curing process, are of high importance since they play a role in flavor development of dry-cured ham. The objective of this study was to analyze the residues of the less-studied metabotropic glutamate receptor 1 (mGluR1) implicated in the recognition of umami dry-cured ham dipeptides by molecular docking simulation using the AutoDock Suite tool. AH, DA, DG, EE, ES, EV, and VG (and glutamate) were found to attach the enzyme with inhibition constants rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…This ensured that our docking simulations were accurate, and minimized the impact of structural errors on our results. Finally, we limited our selection to PDB structures of Homo sapiens to ensure that our results were relevant to the human system 45 . Further, the docking protocol was validated through the process of docking using the internal ligands extracted from the obtained PDB IDs of the target candidates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This ensured that our docking simulations were accurate, and minimized the impact of structural errors on our results. Finally, we limited our selection to PDB structures of Homo sapiens to ensure that our results were relevant to the human system 45 . Further, the docking protocol was validated through the process of docking using the internal ligands extracted from the obtained PDB IDs of the target candidates.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we limited our selection to PDB structures of Homo sapiens to ensure that our results were relevant to the human system. 45 Further, the docking protocol was validated through the process of docking using the internal ligands extracted from the obtained PDB IDs of the target candidates. The protocol with the best docking pose of the internal ligand as reported in the respective PDB was chosen.…”
Section: Molecular Docking Using Molecular Operating Environment (Moe)mentioning
confidence: 99%
“…Even umami dipeptides GS, KP, PN, and SY have been identified in hydrolysates from porcine bone protein extracts [ 105 ]. Finally, dry-cured ham-occurring dipeptides AH, DA, DG, EE, ES, EV, and VG have also been evaluated in in silico molecular docking against mGluR1, reporting glutamate-like interactions, but the data also revealed that other residues from the receptor might be involved in the docking with the ligands [ 87 , 106 ].…”
Section: Taste Of Di- and Tripeptidesmentioning
confidence: 99%
“…Because bitter-tasting amino acids are generally hydrophobic, it would not be surprising if an abundance of hydrophobic peptides strongly affects the flavors of foods such as still-ripening and well-matured cheeses. As for savory foods, most of them result from protein hydrolysis that occurs in long-cooked foods, fermented foods such as soy, fish, oyster sauces, and miso pastes, and long-matured foods such as cheese and cured meat. It is now well-accepted that amino acids and peptides contribute significantly to the overall taste of savory foods . While single amino acids are likely to form aroma compounds during thermal and microbiological processing, , peptides may remain more stable and can contribute to taste depending on process parameters.…”
Section: Introductionmentioning
confidence: 99%